Mali : Technical Assistance Report-Mining Taxation: Modeling of Five Mining Operations. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses Malian mining taxation. Mali's industrial mining sector is predominantly gold mining, with six industrial mines currently active. Most of the mines are old, but some have substantial reserves; extensions are planned for the Syama, Morila, Kalama, Tabakoto-Segela, and Loulo-Gounkoto mines. The Fiscal Analysis for Resource Industries model was completed for five new projects with recent feasibility studies. The government revenue contributed by the five new projects is on the order of USD 1.7 billion (constant dollars) over the next 10 years. The application of the 1999 or 2012 Mining Code increases the government's share of income in comparison with the 1991 code.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Mauritania, Islamic Republic of